Surface Modification of Titanate Nanotubes with a Carboxylic Arm for Further Functionalization Intended to Pharmaceutical Applications - Ranim Saker; Orsolya Jójárt-Laczkovich; Géza Regdon; Tamás Takács; Imre Szenti; Noémi Bózsity-Faragó; István Zupkó; Tamás Sovány (MDPI AG, 2023)
Nanotechnology is playing a significant role in modern life with tremendous potential and promising results in almost every domain, especially the pharmaceutical one. The impressive performance of nanomaterials is shaping the future of science and revolutionizing the traditional concepts of industry and research. Titanate nanotubes (TNTs) are one of these novel entities that became an appropriate choice to apply in several platforms due to their remarkable properties such as preparation simplicity, high stability, good biocompatibility, affordability and low toxicity. Surface modification of these nanotubes is also promoting their superior characters and contributing more to the enhancement of their performance. In this research work, an attempt was made to functionalize the surface of titanate nanotubes with carboxylic groups to increase their surface reactivity and widen the possibility of bonding different molecules that could not be bonded directly. Three carboxylic acids were investigated (trichloroacetic acid, citric acid and acrylic acid), and the prepared composites were examined using FT-IR and Raman spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and dynamic light scattering (DLS). The toxicity of these functionalized TNTs was also investigated using adherent cancer cell lines and fibroblasts to determine their safety profile and to draw the basic lines for their intended future application. Based on the experimental results, acrylic acid could be the suitable choice for permanent surface modification with multiple carboxylic groups due to its possibility to be polymerized, thus presenting the opportunity to link additional molecules of interest such as polyethylene glycol (PEG) and/or other molecules at the same time.